2017
DOI: 10.2500/ajra.2017.31.4423
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathologic Characteristics of Nasal Polyps in Adult Koreans: A Single-Center Study

Abstract: The immunopathologic characteristics differed between eosinophilic NP and noneosinophilic NP and between atopic NP and nonatopic NP. The different underlying pathogenic processes may influence the development of Korean NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…4,5,11 Our finding of higher fibronectin in NE-CRS subjects compared to the other CRS groups is consistent with the results that were reported by Shin et al. 16 who found the highest levels of fibronectin RNA and protein in noneosinophilic polyps from Korean subjects. There was no difference in collagen IV expression among any of the groups.…”
Section: Discussionsupporting
confidence: 91%
“…4,5,11 Our finding of higher fibronectin in NE-CRS subjects compared to the other CRS groups is consistent with the results that were reported by Shin et al. 16 who found the highest levels of fibronectin RNA and protein in noneosinophilic polyps from Korean subjects. There was no difference in collagen IV expression among any of the groups.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, there are several studies that addressed MMP-9 elevation in ECRS. For instance, Shin et al 30 showed that MMP-9 mRNA expression increased significantly in nasal polyps derived from patients with CRSwNP. In addition, we have previously shown that eosinophil granule protein acts on nasal epithelial cells to enhance MMP-9 production.…”
Section: Discussionmentioning
confidence: 99%
“…Chain Reaction (PCR) (26,41,46,49,54,(56)(57)(58) and Western Blot analysis (13,29,46,49,53,54,57,59,62) were also selected by several researchers, while immunofluorescence (27,34,37,57) , Northern blot analysis (23) and Luminex (60,61) were used in a minority of studies. It is however of note that in studies where multiple methods were applied (quantitative) m-RNA and protein levels were reported to be in consistency with each other and with semi-quantitative or qualitative immunohistochemical results (26,34,41,49,57,62) .…”
Section: Studymentioning
confidence: 99%
“…Lechapt-Zalcman 2001 for all & 88-84Kd, 22 Chen 2007, 26 Can 2008, 28 Eisenberg 2008, 29 Kahveci 2008, 30 Bugdayci 2010 (allergic NP-plasma) 32 Li 2010, 34 Wang 2012, 38 2013 42 in gl of pri, Wang 2013 in gl of rec, 42 De Borja Callejas 2013 in ECM &eos, 39 Malinsky 2013, 40 Yeo 2013 rec>pri> controls, 43 Li 2015 III>II>I>controls, 46 Shin 2017 atop & non-atop, 54 Chen 2018 56 Lechapt-Zalcman 2001 for 92kD, 22 Bugdayci 2010 (non-allergic NP-plasma), 32 Van Crombruggen 2012, 37 Wang 2012, 38 Can 2008, 28 Li 2010, 34 Van Crombruggen 2012, 37 Chen 2018 56 (pri-mucus), 27 Kahveci 2008 30 Katainen 2015 (sec) 45 Kostamo 2007 (rec-mucus), 27 28 Kahveci 2008, 30 Yeo 2013 (rec & pri) 43 Chen 2007, 26 Li 2010, 34 De Borja Callejas 2013, 39 Katainen 2015 (sec & serum), 45 Vetuschi 2020 (different distribution) 62 none Li 2010 34 Can 2008 28 TIMP-2 Li 2015 (controls>I>II &III) 46 Li 2010, 34 Eyibilen 2011, 36 Katainen 2015 (sec & serum) 45 none Eyibilen 2011 36 Li 2010 34 MMP-9/TIMP-2 Katainen 2015 (sec) 45 Katainen...…”
Section: Mmp-9mentioning
confidence: 99%